DIGITAL LEADERSHIP AND SAFETY CLIMATE ENHANCE OPERATIONAL PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT IN PUBLIC MARITIME SERVICES - Abdul Wahid; Siti Maria; Anisa Kusumawardani (CV. Radja Publika, 2026)
This study analyzes the influence of digital leadership and safety climate on operational performance through organizational commitment at the Tanjung Santan Class III Port Operational Unit Office. This study departs from the global debate on the effectiveness of digital transformation and safety strengthening in improving the reliability of high-risk public sector operations. A conceptual model was built by integrating the perspectives of resource-based view, dynamic capability, and social exchange theory to explain the commitment-based causal mechanism. Data were collected through a survey of 33 employees and analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that digital leadership and safety climate have a significant effect on organizational commitment and improve operational performance both directly and indirectly. Commitment acts as a partial mediator that strengthens the relationship between the two exogenous variables and the performance. These findings confirm that operational reliability is supported by the integration of managerial capabilities, a safe work climate, and psychological engagement of employees.